Fantástico decolonial em Teresa decide falar de Lindevania Martins - SILVA, Patricia de Sousa (2025)
The work in question is an investigation from the perspective of decolonial studies, which analyzes how Fantasy Literature tends to be a potential strategy for criticizing the logic of colonialities in the fantasy stories “Teresa Decide Falar”, “No meio da testa”, “Ossos do ofício” and “A substituta”, from the book Teresa Decide Falar (2022), authored by Lindevania Martins who, as a black and Maranhão writer of contemporary literature, has been a crucial representative of the voices marginalized and stereotyped by patriarchal supremacy. In addition, this work aims to point out the intersections between colonialism, patriarchy and the social constructions of gender that plague the lives and daily lives of the characters in the stories in question. To this end, a qualitative, bibliographical and exploratory approach was taken in the search for aspects of literary fiction of the fantastic genre/mode that corroborate the theme and understanding of the concepts discussed throughout the dissertation. In this sense, the adopted methodology aims at the appropriate understanding of the concepts of coloniality, decoloniality, intersectionality and how these phenomena can be studied in fantasy literature texts. To this end, as a basis, works by the following thinkers were studied: Heleieth Saffioti (1987; 2015), María Lugones (2020), Rita Laura Segato (2012), Lélia Gonzalez (2020), Susana de Castro (2020), Aníbal Quijano (2005), Walter Mignolo (2017; 2018), Maldonado-Torres and Grosfoguel (2018), Kimberle Crenshaw (2002), Tzvetan Todorov (1970; 2004), Ana Luiza Silva Camarani (2014); Marisa Martins Gama-Khalil (2013), Irène Bessière (2009), among other scholars who theorize about the themes listed. Furthermore, the results point to the way in which the contemporary author from Maranhão reveals the violence exercised against subalternized subjects, especially women; however, although they suffer oppression, some characters present decolonial practices of reexistence in the fight against the Colonial Matrix of Power.